Socially Necessary Rail Services - Cole, Stuart; Holvad, Torben (Proceedings from the Annual Transport Conference at Aalborg University, 1999)
Rail services across Europe are facing problems due to declining market share, lack of responsiveness to market changes and customers’ needs. Policy initiatives are put forward to change this situation and provide viable solutions, e.g. as presented in the EC White Paper from 1996 on Revitalising the Community’s Railways. Many rail services are loss-making and will continue to be so such that these services can only be provided through financial support from the State. Given that resources are scarce it is important that this support is allocated according to the social value from these services. This paper will present the EC funded SONERAIL project, which has concerned an examination of socially necessary rail services. In particular, it has developed an evaluation methodology which allows for the assessment of the costs and benefits associated with providing a given rail service. The paper is planned as follows. Section 1 will give an overview of the SONERAIL project in terms of background, objectives and project structure. In section 2 the SONERAIL definition of a socially necessary rail service will be described. The evaluation methodology developed during the project will be examined in section 3. Subsequently, section 4 will discuss the potential for applying the methodology in practice. Section 5 considers possible future scenarios while best-practice recommendations regarding the provision and evaluation of socially necessary rail services are given in section 6.